Regímenes de Integración Regional: La construcción institucional de los mercados del sur global - Palestini Céspedes, Stefano (Revista de Sociología, 2012)
The essay introduces the concept of regional integration regime as an analytical tool for the comparative study of integration processes in emergent economies. Using this concept, the author analyzes in first place the historical path of regional integration in South America and Southeast Asia, establishing the structural relations between regional integration and capitalist development. In second place, the institutional characteristics of contemporary integration regimes are described. The paper concludes advancing some hypotheses –based on political economy– about the depth of the integration and the nature of change within these regional regimes.